Dekonstruksi Hukum Perkawinan Dalam Islam: Analisis Kritis Terhadap Praktik Kawin Kontrak Di Era Modern: Dekonstruksi Hukum Perkawinan Dalam Islam: Analisis Kritis Terhadap Praktik Kawin Kontrak Di Era Modern - Mustafa, Fitri; Fuad , Fokky; Mawariza , Putri; Suthon , Habib; Aziz, Jhon Kenedy (Yapilin Press, 2025)
The practice of contract marriage or muwaqqat marriage raises complex problems in the contemporary Islamic legal and ethical order. This article examines this phenomenon from the perspective of classical and contemporary jurisprudence, maqāṣid al-syarī'ah, as well as positive legal regulations in Indonesia. This study shows that contract marriage is not only contrary to the principle of mitsāqan ghalīẓan in Islam, but also has social implications that are detrimental to women and children, especially due to the absence of legal protection. The disharmony between Islamic law and national law exacerbates this situation, exacerbated by the absence of explicit regulations prohibiting the practice. A deconstructive approach to marriage law is needed to dismantle the permissive legal structure against covert exploitation. Through the framework of maqāṣid al-shari'ah and progressive Islamic ethics, this article offers a new legal construction that is just, responsive, and in favor of vulnerable groups. The results of this study are expected to make a real contribution to the advocacy of family law policies based on the values of substantive justice and the protection of human rights.